Animals in Environmental Education Interdisciplinary Approaches to Curriculum and Pedagogy - Lloro-Bidart, Teresa; Banschbach, Valerie S.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This book explores interdisciplinary approaches to animal-focused curriculum and pedagogy in environmental education, with an emphasis on integrating methods from the arts, humanities, and natural and social sciences. Each chapter, whether addressing curriculum, pedagogy, or both, engages with the extant literature in environmental education and other relevant fields to consider how interdisciplinary curricular and pedagogical practices shed new light on our understandings of and ethical/moral obligations to animals. Embracing theories like intersectionality, posthumanism, Indigenous cosmologies, and significant life experiences, and considering topics such as equine training, meat consumption and production, urban human-animal relationships, and zoos and aquariums, the chapters collectively contribute to the field by foregrounding the lives of animals. The volume purposefully steps forward from the historical marginalization of animals in educational research and practice.
1. Introduction to Animals in Environmental Education: Whither Interdisciplinarity? -- Part I Intersectional Perspectives -- 2. What Can an Animal Liberation Perspective Contribute to Environmental Education? -- 3. An Intersectional Approach to Teaching and Learning About Humans and Other Animals in Educational Contexts -- 4. Intersectional and Interdisciplinary Approaches to Interspecies Food Justice Pedagogies -- Part II Posthumanism -- 5. Mutual Becomings? In Search of an Ethical Pedagogic Space in Human-Horse Relationships -- 6. Co-mingling Kin: Exploring Histories of Uneasy Human-Animal Relations as Sites for Ecological Posthumanist Pedagogies -- 7. Attending To Nonhuman Animals In Pedagogical Relationships and Encounters -- Part III Arts-Based Approaches -- 8. The Call of Wild Stories: Crossing Epistemological Borders with Narrative Fiction -- 9. On the Origin of the Dragon: Evolving a Transdisciplinary Research Pedagogy -- 10. Coexisting Entities in Multispecies Worlds: Arts-Based Methodologies for Decolonial Pedagogies -- Part IV Interdisciplinary Conversations in Formal and Non-Formal Education -- 11. Connecting Animal Cognition and Emotion with Ethical Reasoning in the Classroom -- 12. Putting Meat on the (Classroom) Table: Problems of Denial and Communication -- 13. Significant Life Experiences and Animal-Themed Education.
Keywords: Curriculums (Courses of study).; Education$1 (BCurricula.s; Education$1 (BPhilosophy.s; Educational policy; Education and state; Environmental education; Curriculum Studies; Educational Philosophy; Educational Policy and Politics; Environmental and Sustainability Education